DEVELOPMENT OF AUGMENTED REALITY TECHNOLOGY-BASED INTERACTIVE LEARNING MEDIA IN CHEMICAL BONDING MATERIALS - Evi Sapinatul Bahriah; Salamah Agung; Ade Irma Nur (Universitas Negeri Surabaya, 2022)
Abstract: This study aims to produce interactive learning media based on augmented reality technology on the concept of chemical bonds and determine student responses to the media. The research method used is the R & D method. The instruments used are material expert validation sheets, media expert validation sheets, and student response questionnaires. The data obtained were analyzed descriptively. Based on the results of material expert validation, an average of 80.41% (feasible category) was obtained and the media expert validation results obtained an average of 90.92% (very feasible category). The results of the limited trial received positive responses from students with details of the percentages obtained, namely 85.75% for the usability aspect, 81.80% for the illustration use aspect, 74.57% for the future impact aspect. 79.64% for the aspect of material usefulness, and 77.20% for the grammatical aspect. Overall, the augmented reality interactive learning media developed received a positive response from students with a percentage of 79.78% and suitable for use in learning.